PENERAPAN STRATEGI MOTIVASIONAL ARIAS DALAM PEMBELAJARAN MENULIS PUISI EPIK MENGGUNAKAN MEDIA FILM - Yanti, Dewi (Universitas Muhammadiyah Jakarta, 2017)
Writing a language skill that requires practice to be controlled properly. writing skills closely related to other skills, such as listening, speaking, and reading. Therefore, learning to write should get more attention that writing skills are considered to be complex and complicated can be mastered easily. On learning Indonesian language and literature, especially in the sixth grade of elementary school, the students began to be introduced to write poetry. There are some things that become obstacles students in writing poetry as a matter of choosing words (diction), the selection of ideas (imagination), and figurative language (figure of speech). These constraints raise the motivation of authors to conduct research by providing learning to write poetry that is attractive and easy to students. In ensuring this research, in addition to the use of the medium of film to stimulate students in writing an epic poem, the author also implements strategies to make students motivated in learning writing that will be implemented. The strategy used the motivational strategies ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction).